Correlation between Consumption Food Sources of Iron and Intake of Iron Tablet on Anemia Cases in Pregnant Women at Bulili Public Health Center: Hubungan Pola Konsumsi Sumber Pangan Zat Besi dan Asupan Tablet Tambah Darah dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Bulili - Wery Aslinda; Putu Candriasih; Yuridesi Nurani Putri (Svasta Harena: Jurnal Ilmiah Gizi, 2021)
Anemia in pregnancy can increase the risk of low birth weight babies, miscarriage, birth prematurely, the risk of bleeding before and/or during delivery which can cause death to mother and baby. This study aims to know the correlation between consumption of food sources of iron and intake of iron tablets on anemia cases in pregnant women at Bulili Public Health Center. This type of research is analytic with a cross-sectional approach. The sample in this study was 39 pregnant women. The data were obtained from interviews and checking hemoglobin levels. Data analysis used univariate and bivariate analysis with the Chi-Square test. The results showed that consumption food sources of iron at Bulili Public Health Center in the rare category (51,3%), intake of iron tablets in the low category (51,3%), and the incidence of anemia in pregnant women (48,7%). While the correlation between consumption food sources of iron (ρ-value= 0,037) and intake of iron tablets (ρ-value= 0,001) on anemia cases in pregnant women at Bulili Public Health Center. The conclusion of this study is that there is a relationship between the consumption of food sources of iron and the intake of iron tablets on anemia cases in pregnant women at Bulili Public Health Center.